Control strivings in the Socio-Economic Panel (SOEP) - Ina Schöllgen; Denis Gerstorf; Jutta Heckhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
The Motivational Theory of Life-Span Development (MTD) identifies motivational and self-regulatory strategies that people use to meet the challenges they face throughout life. The theory distinguishes control strivings related to goal engagement from those related to goal disengagement and goal reengagement. In the Innovation Sample of the Socio-Economic Panel (SOEP-IS), these control strivings were surveyed using 12-item scales for key domains of life: work, family, and health. In this report, we first present key concepts and principles of MTD and a brief overview of research using the theory. This provides the backdrop for our discussion of the relevance of control strivings for major thematic areas covered in the SOEP and for the proposed domain-specific assessment of control strivings. Second, we examine the reliability and factor structure of the scales, using data from the SOEP Innovation Sample collected in 2012. In a third and finalstep, we sketch possible projects that make use of the rich SOEP data so as to examine pivotal questions revolving around the nature of control strivings (changes) across adulthood and old age as well as their antecedents, correlates, and consequences. In line with predictions based on MTD, results revealed mostly moderate to high inter-item correlations for selective primary control, selective secondary control, and compensatory primary control, with all items loading on a single goal engagement factor. Our results further show that disengagement, self-protection and re-engagement are interrelated, but distinguishable strategies for dealing with unattainable goals.
Keywords: C81; Z13; 330; primary and secondary control; goal engagement; goal disengagement; life-span development; motivation; SOEP; SOEP-IS